In vitro evaluation of the effect of Pluchea indica extracts in promoting glucose consumption activity on a liver cell line - Suriyah, Wastuti H; Ichwan, Solachuddin J A; Kasmuri, Abdul R; Taher, Muhammad (UI Scholars Hub, 2019)
Background: Type 2 diabetes mellitus is a chronic metabolic disorder that is associated with mortality and morbidity. Recently, several plant-based agents have been used in the management of diabetes. Pluchea indica has been traditionally consumed as a medicinal plant in Southeast Asia, and its leaves have demonstrated induction of hypoglycemic effect in normal rats. This in vitro study aimed to evaluate the potency of P. indica extracts in stimulating glucose consumption in human liver CCL-13 cell line model. Methods: P. indica leaves were dried and extracted using a series of organic solvents and water. The effect of the extracts on cell viability was determined by MTT assay. The glucose consumption was analyzed using glucose oxidase method. Results: Our results revealed that the methanol extract of P. indica could significantly increase glucose consumption of cells in a concentration-dependent manner, which suggests the usefulness of the extract as an antidiabetic candidate via stimulation of glucose uptake into the liver cells. Conclusion: Our study suggests that P. indica is a potential natural candidate for diabetes mellitus management.